A Phosphotyrosine Switch in Estrogen Receptor β Is Required for Mouse Ovarian Function - Yuan, Bin; Yang, Jing; Dubeau, Louis; Hu, Yanfen; Li, Rong (Frontiers in Cell and Developmental Biology, 2021)
The two homologous estrogen receptors ERa and ERβ exert distinct effects on their cognate tissues. Previous work from our laboratory identified an ERβ-specific phosphotyrosine residue that regulates ERβ transcriptional activity and antitumor function in breast cancer cells. To determine the physiological role of the ERβ phosphotyrosine residue in normal tissue development and function, we investigated a mutant mouse model (Y55F) whereby this particular tyrosine residue in endogenous mouse ERβ is mutated. While grossly indistinguishable from their wild-type littermates, mutant female mice displayed reduced fertility, reduced ovarian cell proliferation, and lower progesterone production. Moreover, mutant ERβ from female mice during superovulation is defective in binding to and activating promoters of its target genes in ovarian tissues. Thus, our findings provide compelling genetic and molecular evidence for a role of isotype-specific ERβ phosphorylation in mouse ovarian development and function.